Pengaruh Pengalaman Kerja dan Keterikatan Kerja Terhadap Kinerja Karyawan pada PT. Trakindo Utama Palembang - Regin Atikah; Mohammad Kurniawan DP; Try Wulandari (CV. Ulil Albab Corp, 2024)
This research is aimed at how the impact of work experience and attachment to work on the performance of employees at PT. Trakindo Utama Palembang. The study used quantitative analysis, a sample used by as many as 60 respondents. The data obtained in this study is through interviews with several employees and the dissemination of questionnaires to all employees. The data analysis technique uses double linear analysis, with test t and test f. However, to see to what extent the accuracy and validity of research variables used test validity and rehabilitation in SPSS version 26. The results of the analysis of test t study obtained a significant value of work experience and work attachment of 0,000 < 0,05, which in part experience work and attachment work have a positive and significant impact on employee performance in PT. Trakindo Main Development. This shows that the better the work experience and work attachment, the higher the employee performance produced by employees at PT. Trakindo Utama Palembang.